2005
DOI: 10.1055/s-2005-867074
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia in Neurological Diseases

Abstract: Insomnia is the most common sleep complaint. Insomnia is not a disease itself but mostly a clinical sign of an underlying disease. Degenerative and vascular diseases involving the central nervous system (CNS) may impair sleep either as a result of the brain lesion or because of illness-related discomfort (motor immobility, social and familial impairment, depression, drugs). Some neurological conditions characterized by movement disorders that start or persist during sleep hinder sleep onset and/or sleep contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Clinical and neurophysiologic patterns similar to those described in this case can be seen in Morvan's disease and in delirium tremens, which combine lack of NREM, especially SWS, with oneirism, prominent autonomic activation and severe motor agitation [50]. Both conditions are characterised, as FFI, by thalamic involvement.…”
Section: Discussionsupporting
confidence: 76%
“…Clinical and neurophysiologic patterns similar to those described in this case can be seen in Morvan's disease and in delirium tremens, which combine lack of NREM, especially SWS, with oneirism, prominent autonomic activation and severe motor agitation [50]. Both conditions are characterised, as FFI, by thalamic involvement.…”
Section: Discussionsupporting
confidence: 76%
“…Among the clinical features of PD are motor impairments involving resting tremor, bradykinesia, postural instability and rigidity along with non-motoric symptoms such as autonomic, cognitive and psychiatric problems [ 83 , 84 , 85 ]. Several studies have demonstrated the high prevalence of sleep disturbances in PD, which in some cases was close to 90% which is correlated to the severity of the disease [ 86 , 87 ].…”
Section: Melatonin Receptor Agonists In Comorbid Neurological Disementioning
confidence: 99%
“…Severe agrypnia usually lasts only a few weeks in about 90% of cases, but occasionally may persist and lead to death; it is associated in most cases with intense anxiety, delirium and often remarkable hallucinatory behavior with enacted dreams [159]. In addition, patients exhibit symptoms of autonomic hypertension and peculiar motor disturbances with agitation, cramps, myoclonic jerks and fasciculations ("fibrillary chorea").…”
Section: Morvan's Fibrillary Choreamentioning
confidence: 99%